Brentuximab vedotin combined with ABVD or AVD for patients with newly diagnosed Hodgkin's lymphoma: a phase 1, open-label, dose-escalation study - Younes, Anas; Connors, Joseph M; Park, Steven I; Fanale, Michelle; O'Meara, Megan M; Hunder, Naomi N; Huebner, Dirk; Ansell, Stephen M (The lancet oncology, 2013)
Roughly 70–80% of patients with advanced stage Hodgkin's lymphoma are cured with various first-line and second-line treatments, including ABVD, BEACOPP, and stem-cell transplantation. Brentuximab vedotin has shown significant clinical activity, with a manageable safety profile, in patients with relapsed or refractory Hodgkin's lymphoma. We aimed to assess the safety and early clinical efficacy of this drug as first-line treatment in combination with standard or modified-standard treatment in patients with previously untreated Hodgkin's lymphoma. We did a phase 1, open-label, dose-escalation safety study comparing brentuximab vedotin in combination with standard (ABVD) or a modified-standard (AVD) treatment. Patients were enrolled into the groups sequentially. Main entry criteria were newly diagnosed, treatment-naive, CD30-positive patients with Hodgkin's lymphoma who had histologically confirmed stage IIA bulky disease or stage IIB–IV disease and an Eastern Cooperative Oncology Group performance status of two or less. Patients received doses of 0·6, 0·9, or 1·2 mg/kg brentuximab vedotin by intravenous infusion every 2 weeks with either ABVD (25 mg/m2 doxorubicin, 10 units/m2 bleomycin, 6 mg/m2 vinblastine, and 375 mg/m2 dacarbazine) or AVD (ABVD modified regimen without the inclusion of bleomycin) for up to six cycles. Our primary objectives were to assess the safety profile and establish the maximum tolerated dose (MTD) of brentuximab vedotin in combination with ABVD and AVD. The safety profile and MTD was assessed for the safety population. The study has completed and the final analysis is presented. This study was registered with ClinicalTrials.gov, number NCT01060904. Between Jan 29, 2010, and Sept 17, 2012, 51 patients were enrolled and received at least one dose of brentuximab vedotin. The maximum tolerated dose of brentuximab vedotin when combined with ABVD or AVD was not exceeded at 1·2 mg/kg. 21 (95%) of 22 patients given brentuximab vedotin and ABVD achieved complete remission, as did 24 (96%) of 25 patients given brentuximab vedotin and AVD. Adverse events were generally grade 1 or 2; however, an unacceptable number of patients in the brentuximab vedotin and ABVD groups had pulmonary toxic effects (11 [44%] of 25), which exceeded the historical incidence for ABVD alone. No patients experienced pulmonary toxic effects when treated with brentuximab vedotin plus AVD. The most common grade 3 or worse events were neutropenia (20 [80%] of 25 patients in the brentuximab vedotin and ABVD group vs 20 [77%] of 26 patients in the brentuximab vedotin and AVD group), anaemia (five [20%] vs three [12%]), febrile neutropenia (five [20%] vs two [8%]), pulmonary toxic effects (six [24%] vs 0), syncope (three [12%] vs two [8%]), dyspnoea (three [12%] vs one [4%]), pulmonary embolism (three [12%] vs 0), fatigue (one [4%] each), and leucopenia (one [4%] each). Serious events occured in 41% of all patients (14 [56%] in the brentuximab vedotin and ABVD group and seven [27%] in the brentuximab vedotin and AVD group). Serious events occurring in 10% of patients or more overall were febrile neutropenia (four [16%] in the brentuximab vedotin and ABVD group vs two [8%] in the brentuximab vedotin and AVD group), and, in the brentuximab vedotin and ABVD group only, pulmonary toxic effects (six [24%]). Brentuximab vedotin should not be given with bleomycin in general or specifically as first-line therapy for patients with treatment naive, advanced stage Hodgkin's lymphoma. 1·2 mg/kg brentuximab vedotin combined with AVD given every 2 weeks was generally well tolerated by patients. At present, a phase 3 trial comparing brentuximab vedotin plus AVD to ABVD alone is ongoing (ClinicalTrials.gov, number NCT01712490) and will formally assess whether brentuximab vedotin plus AVD might redefine therapy in treatment-naive patients with Hodgkin's lymphoma. Seattle Genetics Inc and Takeda Pharmaceuticals International Co.